7L‐SCBI topology with minimal semiconductor device count. Issue 14 (1st November 2020) - Prathap Reddy, Bhimireddy; Siddique, Marif Daula; Iqbal, Atif; Mekhilef, Saad; Rahman, Syed; Maroti, Pandav Kiran
Abstract : In this work, a seven‐level switched capacitor boost inverter (7L‐SCBI) is proposed with minimal resource count. The proposed inverter requires only eight switches and two capacitors to generate a seven‐level voltage. The proposed 7L‐SCBI is capable of generating a multilevel voltage as well as boost the input DC‐link voltage up to 1.5 times with a reduced blocking voltage of switches and capacitors. The comparison in terms of efficiency and device count with other switched capacitor topologies is presented in detail. The performance validation of the proposed 7L‐SCBI is done with the help of a laboratory prototype.